Work Motivation in Government Bureaucracy: Psychological Factors Affecting Employee Performance - Bakri Hasanuddin; Widiyarsih Widiyarsih; Ahmad Hapid T. A. (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This article investigates the psychological factors that contribute to the work motivation of government employees, with a focus on perceptions of autonomy in work, satisfaction with working conditions, satisfaction of intrinsic needs, and social support and work relationships. The research was conducted through an online survey involving employees at various levels and departments. The questionnaire is designed to measure psychological variables that have the potential to influence work motivation, such as perception of autonomy in work, level of satisfaction with working conditions, and level of satisfaction with intrinsic needs. In addition, demographic data such as age, gender, and position level were also collected for further analysis. Data analysis was carried out with the help of statistical software, including regression analysis, to identify the relationship between psychological variables and work motivation. The results of this research present significant findings that illustrate how these psychological factors influence work motivation in government bureaucracy.